Eagle Syndrome A Comprehensive Review of Pathophysiology, Diagnosis and Management Strategies - Górski, Szymon; Okupniarek, Joanna; Bartosik, Michalina; Jętasiewicz, Igor; Oborski, Michał; Oborski, Krzysztof; Miarczyński, Jakub (Quality in Sport, 2025)
Eagle syndrome, also known as elongated styloid process syndrome, is a rare condition resulting from excessive elongation of the styloid process or calcification of the stylohyoid ligament. These abnormalities may compress adjacent neural and vascular structures, producing a wide range of symptoms such as throat, ear or facial pain, dysphagia, or the sensation of a foreign body in the throat. Due to the proximity of critical anatomic structures and the nonspecific clinical presentation, Eagle syndrome poses a significant diagnostic challenge and should be considered in the evaluation of craniofacial and cervical pain.